Library management : a case study approach - Green, Ravonne A. (Chandos information professional series., 2007)
An essential reference for professionals within the Library and Information Science field, this book provides library managers with the requisite skills to utilize the case study approach as an effective method for problem solving and deliberation. The first chapter discusses the case study as a research tool. The second chapter outlines the processes involved in conducting a case study. An actual case model is presented in the third chapter. The succeeding chapters include case studies written by library management students at Valdosta State University in the USA. The chapters include discussion questions, analyses, and alternative scenarios to provoke further thought and discussion. Written from a practitioners perspectiveDraws on the authors wide-ranging practical experience as a library directorGuides the reader though the case study process.